Chemotactic Guidance of Synthetic Organic/Inorganic Payloads Functionalized Sperm Micromotors. Issue 1 (4th December 2017) - Chen, Chuanrui; Chang, Xiaocong; Angsantikul, Pavimol; Li, Jinxing; Esteban‐Fernández de Ávila, Berta; Karshalev, Emil; Liu, Wenjuan; Mou, Fangzhi; He, Sha; Castillo, Roxanne; Liang, Yuyan; Guan, Jianguo; et al.
Abstract: The preparation and operation of free swimming functionalized sperm micromotors (FSFSMs) as intelligent self‐guided biomotors with intrinsic chemotactic motile behavior are reported. The natural sperm biomotors are functionalized with a wide variety of synthetic nanoscale payloads, such as CdSe/ZnS quantum dots, doxorubicin hydrochloride drug coated iron‐oxide nanoparticles, and fluorescein isothiocyanate‐modified Pt nanoparticles via endocytosis. The FSFSMs display efficient self‐propulsion in various biological and environmental media with controllable swarming behavior upon exposure to a chemical attractant. As a new class of environmentally responsive smart biomotors, the control of the FSFSM speed is achieved by varying the solution osmolarity that leads to different flagellar lengths. High drug loading capacity and responsive release kinetics are obtained with such sperm biomotors. The transport of synthetic cargo can be guided by the intrinsic chemotaxis of the FSFSMs. The chemotactic characteristics, speed control mechanism, and responsive payload release of the FSFSMs are investigated. Such use of free swimming functionalized sperm cells as intelligent microscale biomotors offers considerable potential for diverse biomedical and environmental applications. Abstract : Free swimming functionalized sperm micromotors (FSFSMs) as intelligent self‐guided biomotors with intrinsic chemotactic motile behavior are presented. The FSFSMs display efficient self‐propulsion in various biological and environmental media with controllable swarming behavior upon exposure to a chemical attractant. Such use of free swimming functionalized sperm cells as intelligent microscale biomotors offers considerable potential for diverse biomedical and environmental applications.